ASOKA V MAKASSAR WASTE BANK'S STRATEGY ON WASTE MANAGEMENT IN MAKASSAR CITY - Syahruddin, Syahruddin; Ikram, Mulkhaeri; Wahyuni, Eka (Sosiohumaniora, 2024)
This research aims to determine the strategy of Waste Bank Unit Asoka V Makassar to manage waste in Makassar City. The research used a qualitative study through observation, interviews, and documentation. The informants and primary data sources of this study are representatives of the Waste Bank Asoka V Makassar managers and the community selected based on purposive sampling techniques. In contrast, secondary data are obtained from documentation studies and various previous studies relevant to the topic of this study—the data is analyzed with three stages of descriptive analysis; data reduction, data presentation, and conclusions. The results of this study indicate that Waste Bank Asoka V Makassar's waste management is running well and innovatively. Some strategies carried out by Waste Bank  Asoka V Makassar in waste management are: conducting massive socialization and collaborating with PT. Pegadaian, introducing waste management innovations and optimizing services. Practically, the results of this study indicate that effective waste management can be achieved through various strategies that involve the community and innovation, as well as the importance of collaboration between the government, fund providers, and the local community. Penelitian ini bertujuan untuk mengetahui strategi Bank Sampah Unit (BSU) Asoka V Makassar dalam pengelolaan sampah di Kota Makassar. Studi ini merupakan penelitian kualitatif dengan menggunkan metode pengumpulan melalui observasi, wawancara dan dokumentasi. Adapun yang menjadi informan sekaligus sumber data primer penelitian ini adalah keterwakilan dari pengelola BSU Asoka V Makassar dan masyarakat yang dipilih berdasarkan teknik porposive sampling, sedangkan data sekunder diperoleh dari studi dokumentasi dan pelbagai penelitian terdahulu yang relevan dengan topik penelitian ini. Data tersebut selanjutnya dianalisis dengan tiga tahapan analisis deskriptif; reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa penegelolan sampah oleh Bank Sampah Asoka V makassar berjalan dengan baik dan inovatif. Adapun  beberapa strategi yang dilakukan Bank Sampah Asoka V Makassar dalam pengelolaan sampah yaitu: melakukan sosialisasi secara massive, bekerjasama dengan PT. Pegadaian, mengenalkan inovasi pengelolaan sampah dan mengoptimalkan pelayanan. Secara praktis, hasil penelitian ini menunjukkan bahwa pengelolaan sampah yang efektif dapat dicapai melalui berbagai strategi yang melibatkan masyarakat dan inovasi, serta pentingnya kolaborasi antara pihak pemerintah, penyalur dana dan masyarakat setempat.